A Patient Chronic Kidney Disease with Complication Subdural Hematome during Hemodialisis Programe - Eka Dharma Putra, I Putu (Greenation Publisher & Yayasan Global Research National, 2025)
Subdural hematoma (SDH) is a critical neurosurgical condition often linked to chronic kidney disease (CKD) patients undergoing hemodialysis (HD). This case report presents a 56-year-old male with CKD stage V and SDH as a complication during HD therapy. The patient experienced a sudden decrease in consciousness following routine dialysis. Diagnostic evaluations revealed chronic subdural hematoma with midline shift, accompanied by chronic nephritis and anemia. Management included burr hole surgery, heparin-free dialysis, and supportive medical therapy. The patient showed significant recovery, highlighting the importance of timely intervention and a multidisciplinary approach to manage SDH in CKD patients undergoing HD. Case report: A 56-year-old male CKD stage V patient on routine HD presented with acute headache and decreased consciousness post-dialysis. CT imaging confirmed chronic SDH with a midline shift. Treatment involved burr hole drainage and heparin-free dialysis. The patient recovered well after four days of hospitalization and resumed dialysis without further complications. Discussion: The pathophysiology of SDH in HD patients involves changes in intracranial pressure and impaired hemostasis due to CKD and dialysis-related factors. The use of anticoagulants further exacerbates bleeding risks. This case underlines the need for careful monitoring, individualized HD protocols, and timely surgical intervention for SDH in CKD patients. Conclusion: This case emphasizes the critical risk of SDH in HD patients, advocating for preventive strategies, including modified dialysis protocols and multidisciplinary care, to mitigate complications and improve patient outcomes.